Teresa de Jesús: A Saint for the 21st Century - Solís Mendoza, Nazaret (Mercurio Peruano, 2019)
Teresa de Cepeda y Ahumada was a woman needed for her time. The sixteenth century demanded people with sufficient strength of mind to face the social and organizational disorders suffered by both the Spanish Empire and the Catholic Church. And she was able to understand and accept the work that had to undertake, knowing that, with failing health, his efforts and sufferings would multiply to test one’s life.